2015
DOI: 10.12659/msm.892317
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Level of DNA Damage and Impaired Repair of Oxidative DNA Damage in Patients with Recurrent Depressive Disorder

Abstract: BackgroundDepressive disorder (DD), including recurrent DD (rDD), is a severe psychological disease, which affects a large percentage of the world population. Although pathogenesis of the disease is not known, a growing body of evidence shows that inflammation together with oxidative stress may contribute to development of DD. Since reactive oxygen species produced during stress may damage DNA, we wanted to evaluate the extent of DNA damage and efficiency of DNA repair in patients with depression.Material/Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 33 publications
4
22
0
Order By: Relevance
“…These results are consistent with those of other authors [914]. In the previous paper, we did not calculate DRE and, therefore, cannot compare this parameter between the present and our previous study [16]. However, the kinetics of DNA damage repair was monitored and showed that the cells from patients recovered more slowly than those of the controls, suggesting that DNA damage was less efficiently repaired in patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are consistent with those of other authors [914]. In the previous paper, we did not calculate DRE and, therefore, cannot compare this parameter between the present and our previous study [16]. However, the kinetics of DNA damage repair was monitored and showed that the cells from patients recovered more slowly than those of the controls, suggesting that DNA damage was less efficiently repaired in patients.…”
Section: Discussionsupporting
confidence: 91%
“…However, the urinary levels of 8-oxoG in patients with milder, non-clinical depression did not differ from the healthy controls [15]. Our previous study utilizing comet assay technique on the PBMCs of patients diagnosed with clinical depression confirmed the presence of not only oxidatively modified purines and pyrimidines but also other types of DNA damage, like DNA strand breaks [16]. Furthermore, we also noted that increased DNA damage in patients with depression might be caused not only by the disease itself but also by the impairments of oxidative DNA damage repair, since we observed that the patients’ cells repaired DNA damage induced by hydrogen peroxide (H 2 O 2 ) more slowly than the controls’ cells [17].…”
Section: Introductionmentioning
confidence: 99%
“…Second, the peripheral blood leukocytes showed significantly lower copy number of mitochondrial DNA (mtDNA) and higher oxidative damage due to higher oxidative stress in MDD patients (Chang et al 2015). Similarly, another study reported higher number of single and double stranded breaks in DNA along with oxidative damage with reduced DNA repair activity in patients with depressive disorder (Czarny et al 2015b). The same group further genotyped single nucleotide polymorphisms (SNPs) of three genes encoding glycosylases, which are essential enzymes for adequate operation of base excision repair (BER).…”
Section: Dna Damage In Mddmentioning
confidence: 88%
“…Other studies also showed an increased level of telomere shortening (Simon et al 2006) and an increased frequency of DNA damage (Andreazza et al 2007). Moreover, depression can alter the ability of a cell to repair damaged DNA (Czarny et al 2015b, Forsberg et al 2015), including a reduced plasma antioxidants, antioxidant enzyme function and total antioxidant capacity (Maes et al 2011). There is a significant decreased activity of antioxidants such as whole-blood reduced glutathione, and decreased levels of antioxidant enzymes such as glutathione peroxidase, erythrocyte SOD and serum heme oxygenase 1 in depressed patients (Rybka et al 2013).…”
Section: Dna Damage In Mddmentioning
confidence: 99%
“…The target gene set focused on aberrant cellular functions associated with inflammation in the context of MDD and included genes that play a role in tryptophan metabolism, lipid metabolism, mitochondrial function, and oxidative stress response. The target genes were chosen based on pathways found to be disrupted in multiple blood and brain MDD studies (Quak et al 2014; Lalovic et al 2010; Czarny et al, 2015; Spinazzola and Zeviani, 2009; Shelton et al, 2011), and gene sets were grouped together based on the functional roles of the target gene products. Importantly, all these genes were expressed in MDD and CTR HDFs at baseline, providing additional evidence that HDFs express genes relevant to cellular dysfunction observed in neuropsychiatric disease as seen in previous studies (Garbett et al, 2015b; Manier et al, 2000; Shelton et al, 2004).…”
Section: Resultsmentioning
confidence: 99%